Expressive gestures [videorecording] - Contemporary Arts Media (Australia : Contemporary Arts Media, 2005)
The focus of the film is on gestures and their'imaginative' application in non-realistic performance. Kriszta Doczy, theatre practitioner and lecturer, has been involved in physical performance across continents for decades. This program focuses on gestures in theater performance with special emphasis on composition and meaning.
DVD format
Keywords: Gesture -- Study and teaching; Theatre; Improvisation (Acting)